(untitled) (Journal of Management & Business Studies, 2025)
State institutions face important modernization challenges due to the demand for quality goods and services, and the need to improve their productivity. Raising awareness among managers about the importance of implementing quality management systems incorporating Artificial Intelligence to improve is essential, since by their nature, they need to achieve standards of efficiency, transparency and responsiveness to meet citizen needs, contribute to solving problems, and face challenges such as resistance to change, bureaucracy and corruption, which hinder continuous improvement and interaction between citizens and the State. The objective of this article is to generate a theoretical framework on Public Administration, Quality Management and Artificial Intelligence, based on the scientific study of these topics, identifying relevant topics, main authors, outstanding publications, countries with the highest academic production, predominant keywords and methodologies used. A mixed approach was used, applying scientometric analysis, systematic literature review, phenomenology, hermeneutic analysis to databases and high-impact scientific articles from the Web of Science (WOS), Scopus and Google Scholar platforms. The research facilitates the understanding of the subject and can serve as input for future research to improve Public Administration. The results, discussions and conclusions reveal the need to adopt disruptive and innovative ontological and epistemological approaches that allow us to better address the challenges and trends of this discipline, and define strategies aimed at strengthening it in order to meet the demands of society.